Assessing cerebrovascular reactivity by the pattern of response to progressive hypercapnia. Issue 7 (3rd April 2017) - Fisher, Joseph A.; Sobczyk, Olivia; Crawley, Adrian; Poublanc, Julien; Dufort, Paul; Venkatraghavan, Lashmi; Sam, Kevin; Mikulis, David; Duffin, James
Abstract: Cerebral blood flow responds to a carbon dioxide challenge, and is often assessed as cerebrovascular reactivity, assuming a linear response over a limited stimulus range or a sigmoidal response over a wider range. However, these assumed response patterns may not necessarily apply to regions with pathophysiology. Deviations from sigmoidal responses are hypothesised to result from upstream flow limitations causing competition for blood flow between downstream regions, particularly with vasodilatory stimulation; flow is preferentially distributed to regions with more reactive vessels. Under these conditions, linear or sigmoidal fitting may not fairly describe the relationship between stimulus and flow. To assess the range of response patterns and their prevalence a survey of healthy control subjects and patients with cerebrovascular disease was conducted. We used a ramp carbon dioxide challenge from hypo‐ to hypercapnia as the stimulus, and magnetic resonance imaging to measure the flow responses. We categorized BOLD response patterns into four types based on the signs of their linear slopes in the hypo‐ and hypercapnic ranges, color coded and mapped them onto their respective anatomical scans. We suggest that these type maps complement maps of linear cerebrovascular reactivity by providing a better indication of the actual response patterns. Hum Brain Mapp 38:3415–3427, 2017 . ©2017 Wiley Periodicals, Inc.